IMPROVING STUDENTSâ WRITING SKILLS THROUGH WRITING JOURNAL ARTICLES - Iftanti, Erna (Pusat Pengembangan Bahasa IAIN Tulungagung, 2016)
In Indonesian context, writing is considered as painful activity indicating that oral culture is much better than writing one. The studentsâ works are sufficiently kept in the libraries, although to publish those is much more worthy. Therefore, it is necessary to improve the studentsâ writing skills through a meaningful way namely writing journal article. This review article is therefore intended to discuss ways of improving studentsâ writing skills through writing journal article. The result of consulting different existing related literature can be concluded that the ability of writing can be variously defined based on the pedagogical objectives and approach. Meanwhile, the skill of writing journal article is classified as one of the writing skills derived from Process/Cognitive approach. Amongst the underlying ways to publish the studentsâ manuscripts is by taking a look at the structure of a journal article, the writing guide and the writing style of a journal publication to which the manuscript is intended to publish. By implementing the above mentioned tips of writing a journal article, the EFL students will not only improve their writing skills but make their works much worthy as well. In a nutshell, in addition to publish the studentsâ works, to write journal article is essential to improve their writing skills.